Digital assessment of the accuracy of implant impression techniques in free end saddle partially edentulous patients. A controlled clinical trial - Mohamed M. Dohiem; Medhat Sameh Abdelaziz; Mohamed Farouk Abdalla; Aya Mohamed Fawzy (BMC, 2022)
Abstract Objectives This in vivo study aims to assess the accuracy of the digital intraoral implant impression technique, the conventional closed-tray impression technique, and open-tray impression techniques in a standardized method of data segmentation along with the best-fit algorithm to overcome the inconsistency of results of previous studies regarding implant impression techniques. Materials and methods Sixteen implants were placed in eight patients. Each patient has undergone four impression techniques: direct intraoral scanning of the stock abutment, intraoral scanning using a scan body, conventional closed tray impression technique, and the conventional open tray impression technique. The conventional impressions were poured into stone casts with analogues and stock abutments and scanned using a desktop scanner. In intraoral scanning of the scan body, computer-aided design software was used for the replacement of the scan body with a custom-made abutment that is identical to the stock abutment, allowing comparison with the other impression techniques. The deviation in implant position between the groups was measured using special 3D inspection and metrology software. Statistical comparisons were carried out between the studied groups using a one-way analysis of variance (ANOVA) test. Results The total deviation between groups was compared to the reference group represented by the intraoral scanning of the abutment. The total deviation was statistically significantly different (P = 0.000) among the different studied groups. The mean deviation was recorded as 21.45 ± 3.3 μm, 40.04 ± 4.1 μm, and 47.79 ± 4.6 μm for the intraoral scanning of the scan body, the conventional closed, and open tray, respectively. Conclusion For implant impressions in partially edentulous patients, intraoral oral scanning using a scan body significantly improves scanning and overall accuracy. Regarding conventional impressions, the closed-tray impression techniques showed more accuracy than conventional open-tray impressions. Clinical relevance Intraoral digital implant impression using scan body offers more accuracy than conventional implant impression techniques for recording posterior implant position in free-end saddle partially edentulous patients.